New Detailed Modeling of GICs in the Spanish Power Transmission Grid. Issue 9 (22nd September 2021) - Torta, J. M.; Marsal, S.; Ledo, J.; Queralt, P.; Canillas‐Pérez, V.; Piña‐Varas, P.; Curto, J. J.; Marcuello, A.; Martí, A.
Abstract: The threat of Geomagnetically Induced Currents (GICs) driven by severe Space Weather looms over technological systems such as power grids. Assessing their vulnerability is thus vital to avoid damages or even disruption of the electrical power supply. This endeavor, however, entails an interdisciplinary approach, ranging from the characterization of the geoelectrical structure of the Earth beneath and around the area of interest, or the modeling of the power network from its parameters and topology, and including the validation of the modeling process by means of (direct or indirect) GIC flow measurements. In this paper, we summarize our current achievements focused on mainland Spain, concentrating on the improvements reached after going from a homogeneous Earth's resistivity to an alternative 3D electrical resistivity distribution approach to geoelectric field computation, which is still in progress because new empirical impedance tensors are needed, mainly at sites in the west of the Iberian Peninsula. The second major achievement has come from the addition of the 220 kV level to the network model. The overall improvement has been validated against real GIC data in one area of the country. The new vulnerability maps show that in some nodes the predicted GIC has been substantially reduced by the sum of both effects. The assessment has been carried out down to the level of the individual windings of each transformer, and examples of the estimated GIC flow are given for substations with numerous power transmission lines converging to them at diverse orientations. Plain Language Summary: The Sun can lead to violent phenomena, expelling huge amounts of energy and matter traveling within the solar wind. When such bursts impact the Earth they can trigger phenomena known as Space Weather events. Current systems of our magnetosphere and ionosphere undergo dramatic variations, giving rise to magnetic fields that reach the surface, where numerous technological systems are deployed. The conductivity of the subsoil determines the geoelectric fields that are mapped along terrestrial conductors such as power networks, railways, or oil and gas pipelines. The geomagnetically induced currents (GICs) thus generated are potentially dangerous and can cause multiple adverse socio‐economic impacts. We develop here an assessment of the vulnerability of the Spanish power network to GICs, thus providing useful products that enable the operators to mitigate their effects. Geomagnetic field measurements are convolved with a newly developed earth resistivity model to provide the geoelectric field. This quantity is then input into an updated and extended model of the power network to have a quasi‐real time estimate of the expected impact and produce new and more accurate vulnerability maps. We have also established points of measure under power lines, aimed at validating both the power grid and the ground resistivity models. Key Points: Improvements are achieved by using a 3D inversion of magnetotelluric (MT) data to derive the electric field and adding the 220 kV level to the network model More accurate geomagnetically induced current (GIC) estimates for all power transmission lines, nodes and transformers are provided The system experiences a reduction in GICs flowing to ground, but at the transformer winding level they exhibit, in general, an augmentation